Three Death Cases Occurred by Blank Cartridge Guns Case Report - Tokdemir, Mehmet; Türkoğlu, Abdurrahim; Kafadar, Hüseyin (The Bulletin of Legal Medicine, 2011)
Blank cartridge guns are purchased for self-protection and to frighten an assailant since it is not possible to distinguish them from a real gun by their appearance and the sound they make. However, it is revealed that blank cartri dge guns might cause deaths and they are not harmless as supposed with presented cases. In this study three autopsies of death cases due to shooting to different body parts from different distances by blank cartridge guns are evaluated. Pellets were removed from all three cases during autopsy. Internal bleeding, internal organs injuries, brain and brain membranes’ bleeding and brain lasseration are detected on traces of pellets. The number inj uries caused by blank cartridge guns are increased by the time. There is need for legislations regulating the restriction of easy acquisition and carrying blank cartridge guns. It is also necessary to train the public about the risk and damage of the blank cartridge guns and forbidding adverti sements through the media. Key words: Blank cartridge guns, death, suicide, homicide.